Career Satisfaction of Malaysian Dentists With Expanded Roles at a Specialist Clinic - Azizi Ab Malek; Nawwal Alwani Mohd Radzi; Muhd Firdaus Che Musa (Elsevier, 2023)
ABSTRACT: Objectives: Public dentists interested in postgraduate studies were required to complete clinical attachments at the Malaysian Ministry of Health (MOH) Dental Specialist Clinic (DSC). This cross-sectional quantitative study aimed to explore career satisfaction (CS) and barriers perceived by Malaysian dentists at Malaysia's MOH DSC. Methods: A total of 208 dentists from DSC nationwide completed an online questionnaire in June 2022. Demographic data and information on dentists' expanded roles were retrieved. Responses on dentists' satisfaction and perceived barriers were collected using a 5-point ordinal scale. Mann-Whitney U and Kruskal-Wallis tests were used to compare the mean rank differences for CS. Factors influencing CS were analysed using multiple logistic regression (MLR) (P < .05). Results: The mean age of the respondents was 32.68 ± 2.48 years. Almost half (49.0%) of the respondents were attached to a non-hospital-based clinic. The majority (72.0%) of them were permanently attached to the DSC. About half of the dentists (51.0%) strongly agreed that they received no financial incentives for their expanded role at the MOH DSC. Dentists attached at a non-hospital-based clinic (P = .046), working with more than 15 years of experience (P = .013), and having 12 to 18 months' duration of attachment (P = .014) were more satisfied. MLR analysis revealed that non-Malay respondents (odds ratio [OR], 1.54; P = .035) and those who applied for scholarships more than 3 times (OR, 1.85; P = .050) were more satisfied. In contrast, more than 19 months at the DSC decreased CS (OR, 0.44; P = .029). Conclusions: Despite having a similar organisational structure, DSC dentists had different satisfaction levels. Dentists' ethnicity, duration of attachment, and frequency of applying for scholarships influenced their CS. Future career advancement plans in the MOH should consider these important influencing factors to ensure the delivery of quality health care from their personnel.